Model Pengajaran One Became Tens dan Penulisan Geguritan di SMA - Sigit Emwe (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2018)
Abstract: This paper describes the teaching model â€œOne Became Tensâ€ and geguritanâ€™s writing in high school. Based on the problems that many high school students who have difficulty writing geguritan. The existence of the Java language subjects of 2004â€™s curriculum requires students fluent on the Java language, and one implementation is to write geguritan. Number of student who are feels alienated with the Java language (although as a mother language) is a condition of concern. â€œOne Became Tensâ€ teaching model is an innovative learning model conducted by the author in teaching geguritan which aims to improve productivity to create geguritan in high school. This is done because the teacher should realize that writing skills rely on language skills that are active and productive. Keywords: Models of learning, Teachers, learners, and Geguritan.